Unionization and Labour Regimes in Canada and the United States: Considerations for Comparative Research - Kettler, David; Struthers, James; Huxley, Christopher (Labour/Le Travailleur, 1990)
Abstract Three principal features distinguish the contemporary state of research in industrial relations. First, the unsettlement of fixed categories in the theoretical study of state and society turns the attention of political theorists towards this politically charged domain of dynamic order. Second, recent developments within the domain itself challenge the principal approaches whose competition has governed the discipline. Third, the elaboration of the discipline itself yields increased recognition of the need for heightened theoretical and methodological self-awareness. The decade of comparative studies of divergent union density rates between the United States and Canada provide materials for an exploration of these theoretical issues, especially in light of the fact that recent analytical consensuses are called into doubt but the most recent tendencies. A comparative approach oriented to a history-sensitive concept of "labour regimes'' offers a method capable of learning from the principal competing analytical strategies, while promoting a more open and reliable research programme than many of those considered. Critical encounters with the work of Lipset, Weiler, Teubner, Panitch and Swartz, and others are complemented by comparative historical study, in order to lay out the main elements of the approach proposed.